The Determination of Teacher Role Modeling, Habituation, School Environment, and Worship Facilities in Shaping Students’ Religious Spirit - Taufik Ismail; Muhammad Afif Zamroni; Zakariyah Zakariyah (LPPM Universitas Ibn Khaldun, Bogor, 2025)
This study analyzes the factors influencing the weak internal awareness of students toward religious values, despite the availability of facilities, structured Islamic Religious Education (IRE) curriculum, and school support at SMAN 1 Pangandaran and SMAN 1 Parigi Pangandaran. The research focuses on the influence of IRE teachers’ role modeling, students’ habituation, the school environment, and worship facilities on the development of students’ religious life. A quantitative causal-comparative approach was employed, involving 567 twelfth-grade students, and data were analyzed using SEM-PLS. The findings reveal that students’ habituation has the strongest influence, followed by teachers’ role modeling and the school environment, while worship facilities showed no significant effect. Differences between the two schools were also identified, particularly in intellectual and ritual aspects of religiosity. These results reinforce Attachment Theory, Social Cognitive Theory, and the concepts of habit loop, place identity, and Glock’s religiosity dimensions. Practically, schools are advised to strengthen teachers’ empathetic role modeling, establish consistent positive habituation, and foster a supportive religious environment.